Seabird abundance and distribution off western iberian waters estimated through aerial surveys - Araújo, Hélder (2022)
Western Iberian waters are important migratory flyways, stopover sites, and wintering areas for several of the world’s seabird species. To describe seabird species composition, distribution, and abundance in these waters, we performed six aerial surveys in September and/or October of each year, 2010–2015, covering 74 840 km2. Using line transect methodology, 27 396 seabird sightings from 17 taxonomic groups were recorded along 10 496.3 nautical miles (19 433 km). Using the program “Distance,” annual and overall abundance estimates were obtained for nine taxonomic groups: Balearic Shearwater Puffinus mauretanicus, Great Shearwater Ardenna gravis, Cory’s Shearwater Calonectris borealis, shearwaters, Northern Gannet Morus bassanus, Sabine’s Gull Xema sabini, Great Skua Stercorarius skua, storm petrels, and Red Phalarope Phalaropus fulicarius. For the six-year period, Northern Gannet was the most abundant species (89 630 individuals, coefficient of variation [CV] = 6.28%), followed by Cory’s Shearwater (25 044 individuals, CV = 7.56%) and Balearic Shearwater (13 632 individuals, CV = 20.81%). The remaining taxonomic groups exhibited variable abundances. Results confirm that the study area is important to several seabird species, providing baseline estimates to inform conservation policies and instruments, such as the Birds Directive or the Marine Strategy Framework Directive.